The verbal complex in subordinate clauses from medieval to modern German - Sapp, Christopher D. (Linguistik aktuell ;, 2011)
This research monograph is an empirical and theoretical study of clause-final verbal complexes in the history of German. The book presents corpus studies of Middle High German and Early New High German and surveys of contemporary varieties of German. These investigations of the verbal complex address not only the frequencies of the word orders, but also the linguistic factors that influence them. On that empirical basis, the analysis adopted is the classic verb-final approach, with alternative orders derived by Verb (Projection) Raising. Verb Raising in these historical and modern varieties is.